Populist online communication: introduction to the special issue. Issue 9 (2nd September 2017) - Engesser, Sven; Fawzi, Nayla; Larsson, Anders Olof
ABSTRACT: Populism continues to gain traction in politics but there has been relatively little research on how it plays out on the Internet. The special issue at hand aims at narrowing this gap of research by focusing on the close relation between populism and online communication. This introduction presents an integrative definition of populism, as well as a theoretical analysis of the interplay between populist communication logic and online opportunity structures. The individual contributions discuss how populist actors may benefit from the Internet. They analyze how political leaders and extreme parties use populist online communication. The authors also shed light on how populist movements may relate to various political parties. They finally demonstrate which groups of social media users are more susceptible to populism than others and what effects populist online communication may have on citizens. We hope that this special issue will contribute to the discussion on what is arguably one of the largest political challenges currently faced by a series of nations around the globe.